Shedding Light on Alopecia Areata in Pediatrics: A Retrospective Analysis of Comorbidities in Children in the National Alopecia Areata Registry. Issue 5 (September 2017) - Sorrell, Jennifer; Petukhova, Lynn; Reingold, Rachel; Christiano, Angela; Garzon, Maria
Abstract: Alopecia areata (AA) is a common autoimmune disease and it is challenging to predict which patients will have severe disease. The purpose of this retrospective study was to identify comorbidities in children enrolled in the National Alopecia Areata Registry. Atopic dermatitis was more common in patients with severe AA than in those with mild disease. The most common autoimmune comorbidities were vitiligo, psoriasis, thyroid disease, and juvenile idiopathic arthritis.